THE USE OF CANNABIDIOL IN PEDIATRIC DENTISTRY PATIENTS WITH AUTISM SPECTRUM DISORDER: INTEGRATIVE REVIEW - Bertoldi , Anna Karolliny Costa; Neto , Walter Bertoldi; Arevalo , Andres Camilo Campo; Santos , Bárbara Sttephanny Silveira; Nunes , Filipe de Souza (Brazilian Journal of Implantology and Health Sciences, 2024)
This research project aims to conduct a literature review on the use of cannabidiol (CBD) in pediatric dental patients diagnosed with Autism Spectrum Disorders (ASD). The focus will be on the intersection between pediatric dentistry and ASD treatment, aiming to fill a substantial gap in the scientific and clinical understanding of the subject. The integrated approach provides a solid foundation for informed decision-making by healthcare professionals, family members, and caregivers. The central problem of the research lies in the need for substantial evidence supporting the efficacy and safety of CBD in this specific patient group. The absence of reliable data poses significant challenges for making informed decisions about the pediatric dental treatment of children with ASD, impacting the quality of life for these patients. Therefore, the adopted methodology will involve a literature search, using exclusively recently published articles from the last 5 years, available in databases such as PUBMED and SCIELO, among other relevant sources. The main objective of this literature review is to assess the efficacy of CBD in managing symptoms associated with ASD in pediatric dental contexts, considering its potential therapeutic benefits and possible side effects. The research aims to fill this gap by establishing a comprehensive investigation into the use of CBD in children with ASD, directing its attention to specific implications for oral health.